The Analysis of Information and Communication Technology, Supply Chain Management, Competitive Advantage, and SMEs Performance - Nafisa, Unesya Lu’luatu; Liestyana, Yuli; Utami, Yekti; Wahyuningsih, Tri; Satmoko, Agung; Tugiyo, Tugiyo (AIBPM Publisher, 2023)
This study analyzed the performance of SMEs influenced by information communication technology, supply chain management, and competitive advantage. The researcher selected the bakpia-producing SMEs in Sleman Regency as the population in this study. This research analyzed the data collected from the questionnaires using SEM (Structural Equation Modeling) analysis method using the SmartPLS v.3.2.7 software. The results of this study show that not all hypotheses are accepted. The first hypothesis is accepted where supply chain management positively affects competitive advantage. Supply chain management also affects SME performance positively; thus, the second hypothesis is accepted. Meanwhile, the third hypothesis is accepted, where information communication technology positively affects supply chain management. Two hypotheses are not accepted. The first is the fourth hypothesis: information and communication technology do not affect competitive advantage. The second is the fifth hypothesis: competitive advantage does not affect SME performance. The research team suggests bakpia-producing SMEs to improve information and communication technology and supply chain management practices.